Glucokinase activity in diabetes: too much of a good thing? - Ashcroft, FM; Lloyd, M; Haythorne, EA (Cell Press, 2022)
Type 2 diabetes (T2D) is a global health problem characterised by chronic hyperglycaemia due to inadequate insulin secretion. Because glucose must be metabolised to stimulate insulin release it was initially argued that drugs that stimulate glucokinase (the first enzyme in glucose metabolism) would enhance insulin secretion in diabetes. However, in the long term, glucokinase activators have been largely disappointing. Recent studies show it is hyperactivation of glucose metabolism, not glucose itself, that underlies the progressive decline in beta-cell function in diabetes. This perspective discusses if glucokinase activators exacerbate this decline (by promoting glucose metabolism) and, counterintuitively, if glucokinase inhibitors might be a better therapeutic strategy for preserving beta-cell function in T2D.